PENGARUH CITRA MEREK PRODUK TERHADAP KEPUTUSAN PEMBELIAN (STUDI KASUS PADA KONSUMEN GEOFF MAX DI KOTA BANDUNG) - Erika Nurmartiani; Muhammad Fahrulrozy (POLITEKNIK PIKSI GANESHA, 2024)
The local fashion industry has faced increasingly intense competition post-pandemic, pushing players to innovate to maintain competitiveness. Geoff Max, a local fashion brand founded in Bandung in 2013 and focused on the youth market, has become one of the well-known brands in Indonesia. However, sales at its offline store in Bandung have declined over the past three years. This study aims to analyze the influence of brand image on purchasing decisions for Geoff Max products in Bandung. Involving 100 respondents through simple random sampling, this research uses quantitative methods, including validity, reliability, correlation, and linear regression tests. Brand image contributes 51.9% to purchasing decisions. Brand image has a significant positive influence on purchasing decisions with a significance level of 0.000 > 0.10. Keywords: Brand Image, Purchase Decision